Corona Wedi Buto: Myth in the Efforts of the Tanggulwelahan Villager Facing Covid-19 - Ifan Andriado; Hamida Zama Rahmatillah; Anis Khoirun Nisa; Joan Hesti Gita Purwasih (Randwick International of Social Science Journal, 2021)
The COVID-19 virus was declared by WHO as a pandemic towards the beginning of 2020. As a result, Indonesia also implemented physical distancing nationally. This condition was responded to quite diverse by the community, one of which was in Tanggulwelahan Village, Tulungagung Regency. Myth is actually an alternative that people use in addressing these conditions. Therefore, researchers apply qualitative research methods (phenomenology) to explain the social construction of myths in the efforts of local communities to deal with COVID-19. Based on the results of interviews, observations, and analyzes using social construction theory the following results are obtained. "Buto" figure is a sacred symbol for the community because it is believed to have supernatural strength so that it can banish various outbreaks of disease. This understanding was formed through the process of externalization, objectification, and internalization that has been going on for generations. Meanwhile, medical information related to COVID-19 is new knowledge, so it is difficult to replace the old knowledge of society which is actually a myth.